Social Media Usage and Its Psychological Impact: A study of Anxiety, Depression, and Stress among Adolescents in Lucknow - Rishi Dikshit; Prof. U.V. Kiran (The Bioscan, 2025)
The increasing use of social media has significantly impacted communication patterns and psychological conditions, particularly among adolescents. A study in Lucknow, India, assessed the impact of social media use on depression, anxiety, and stress among 15-19-year-olds. The study used a cross-sectional quantitative design and 253 adolescents, primarily from rural areas. Results showed gender differences, with women experiencing more depression, anxiety, and stress than men. Higher social media use was associated with higher depression and stress scores, and a positive trend for anxiety. Linear regression confirmed social media use as an independent predictor of psychological distress, with moderate explanation. The study emphasizes the need for local mental health interventions, digital literacy courses, and gender-sensitive psychological interventions to counteract the negative impacts of problematic social media use during teenage years. It also underscores the need to address the rural-urban digital divide to promote positive mental health among Indian adolescents.